2020
DOI: 10.1111/vru.12829
|View full text |Cite
|
Sign up to set email alerts
|

CT and radiographic evaluation of bronchial collapsibility at forced expiration in asymptomatic brachycephalic dogs

Abstract: Bronchial collapse due to bronchomalacia is an important cause of chronic coughing in dogs. Radiographic and CT evidence of bronchial collapse has previously been reported in healthy Beagle dogs under forced expiration. However, published studies in brachycephalic dog breeds that are prone to bronchial collapse are currently lacking. In the present prospective analytical experimental study, CT and radiography were used to measure the bronchial diameter and collapsibility of each pulmonary bronchus during end‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
2
13
2
1
Order By: Relevance
“…18 It was also reported that the left-sided bronchi collapsed more than the right, but of the right-sided bronchi, the right middle bronchus collapsed the most. 7,18 In our study, there was not a clear distinction in the amount of collapse between right and left-sided bronchi. However, the right middle bronchus exhibited a high degree of collapse in both healthy and clinical dogs.…”
Section: Discussioncontrasting
confidence: 71%
“…18 It was also reported that the left-sided bronchi collapsed more than the right, but of the right-sided bronchi, the right middle bronchus collapsed the most. 7,18 In our study, there was not a clear distinction in the amount of collapse between right and left-sided bronchi. However, the right middle bronchus exhibited a high degree of collapse in both healthy and clinical dogs.…”
Section: Discussioncontrasting
confidence: 71%
“…Resistance to upper airway flow causes more negative pressures within the oro‐, naso‐, and laryngopharynges, mediastinal airway and esophagus, and lungs and pleural space causing hiatal hernia and reflux of gastric acid into the esophagus 12,14,46 . The prevalence of hiatal hernia in this study (21%) was substantially lower than in BC dogs (44%); however, prevalence was similar when only cats with categories III and IV brachycephaly were considered (44%) 14 .…”
Section: Discussionmentioning
confidence: 50%
“…Some studies used CT to assess airway collapse of the mainstem bronchi, lobar bronchi or both, with no metrics applied to the segmental and subsegmental bronchi, which is the definition of BM used in our study 13,14,26,27 . Artificial forced expiration using syringes to aspirate air from intubated dogs does not mimic the physiology of tidal breathing 14,27 and differs from the paired I/E : BH CTs performed in our study. These ventilator assisted breath‐holds allow comparison of inspiratory and expiratory CT scans to assess changes in airway caliber and the peribronchial lung parenchyma 6‐8 .…”
Section: Discussionmentioning
confidence: 95%
“…Limited studies using CT to diagnose BM are available. Some studies used CT to assess airway collapse of the mainstem bronchi, lobar bronchi or both, with no metrics applied to the segmental and subsegmental bronchi, which is the definition of BM used in our study 13,14,26,27 . Artificial forced expiration using syringes to aspirate air from intubated dogs does not mimic the physiology of tidal breathing 14,27 and differs from the paired I/E : BH CTs performed in our study.…”
Section: Discussionmentioning
confidence: 95%